On the Effects of InterSector Productivity Growth Differences on Sectorial Inflation in the Baltic States Relative to the Euro Area - Bukevičiūtė, Lina (Ekonomika, 2006)
The ability of the Baltic States to damp the growth of inflation might partly depend on the scale of the Balassa-Samuelson (BS) effect. In recent years, inflation was lower in the Baltic States as compared to the beginning of the transition period. This raises the question whether the BS impact on inflation is still relevant. Based on an empirical assessment, this paper aims to provide some recent evidence concerning the productivity growth pattern in the tradable and non-tradable sectors in the new Member States vis-a-vis the euro area. Thus, the paper analyses whether the main assumptions in the Balassa-Samuelson effect of a higher growth of productivity in the tradable sector and a higher wage growth in the non-tradable sector have come true.